Acute cerebellitis caused by Herpes Simplex virus - Campos, Lillian Gonçalves; Duarte, Juliana Avila; Rossato, Roberto; dos Santos, Rodrigo Pires; Vedolin, Leonardo (Clinical and Biomedical Research, 2019)
Case presentation A 29 year-old woman presented to the emergency with gait imbalance and dysarthria. At admission, neurologic examination revealed normal cognition, ataxia, dysarthria, dysmetria on both sides of the body, bilateral vertical nystagmus and loss of the lateral eye movement. Blood examination was notable for a increase in WBC count and demonstrated erythrocyte sedimentation rate of 18 mm/h. Examination of cerebral spinal fluid (CSF) revealed a protein concentration of 166 mg/ dL, a glucose concentration of 56 mg/dL, and pleocytosis. Serum glucose concentration was 126 mg/dL. The patient had no history of immunosuppression or another comorbidity and anti-HIV test was negative. Neurological evaluation included a head computed tomography (CT) scan which revealed normal findings. An MRI of the brain revealed bilateral increased signal intensity in the cerebellum on fluid-attenuated inversion recovery images (FLAIR)/T2, without contrast enhancement, suggesting an inflammatory process confined to the cerebellum (Figure 1 and 2). Furthermore, the cerebellar cortex appeared swollen, a finding consistent with diffuse cerebellitis. There were no alterations in the brainstem. Initially, the possibility of bacterial rhomboencephalitis caused by Listeria monocytoges was considered, since it is the most commom cause of rhomboencephalitis. After a few days with antibiotic therapy (ceftriaxone and ampicillin), polymerase chain reaction (PCR) test of the CSF was positive for Herpes Simplex Virus 1/2 (HSV). Bacterial culture of CSF samples showed no growth, and the results of Gram staining of CSF were negative. Anti-Listeria antibody was also negative and ampicillin discontinued. CSF PCR analysis for other herpesviruses (varicella-zoster virus, Epstein-Barr virus, cytomegalovirus, and human herpesvirus types 6–8) and enteroviruses were also negative. Upon treatment with acyclovir (50 mg/kg/day) during 21 days, symptoms improved. One month later after the first MRI, a significantly reduce of imaging abnormalities was detected (Figure 3).